Terapia de aceptación y compromiso en el trastorno obsesivo compulsivo. - Chugcho Chugcho, Wellington Bernardo (2025)
Obsessive-Compulsive Disorder (OCD) significantly impacts the quality of life of those who suffer from it. Its symptoms, being ruminative and intrusive, interfere with the performance of daily activities, negatively affecting social, family, and work life. For this reason, the implementation of Acceptance and Commitment Therapy (ACT) is important, as it increases psychological flexibility in individuals, allowing them to learn new ways to cope with their thoughts and emotions. The objective of this research was to characterize ACT in OCD through a descriptive bibliographic review, based on 205 selected scientific articles, of which 33 were evaluated for their methodology using the CRF-QS instrument. Among the main findings, factors predisposed to the onset of OCD are identified, with women being more prone than men. Family history, complications during childbirth, and experiencing physical or emotional violence in childhood increase the likelihood of a diagnosis of this disorder. Meanwhile, in ACT, various techniques used in the psychotherapeutic process are evident, which enhance cognitive flexibility in individuals and reduce obsessive-compulsive symptoms. Furthermore, ACT shows better results compared to other therapies. In conclusion, the identification and description of contributing factors enable early diagnosis of this condition. This early diagnosis facilitates intervention through ACT and its various techniques, which promote significant and positive changes in patients' quality of life.